Kasus Kasus di Indonesia White Color Crime (WCC) - Husnil Mubarok Nst; Linda Safitri Lubis; Isna Damayanti Siagian; Sahlan Sahlan (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
White-collar crime has been defined by Edwin Sutherland as "crimes committed by persons of honor and high social status in his work" (1939). White collar crime, almost as perceived by corporate crime because that is done by way of fraud, bribery, embezzlement, computer crime, copyright infringement, money laundering, identity theft, and counterfeiting money. The research method is literature study, and to find out how the types of crimes that are categorized as "white collar crime", the result is the application of laws given to perpetrators of crime "white collar crime", has been providing justice and legal certainty to the community.